Most of the popular rice varieties in Bangladesh are of medium glycemic index (GI) - Tamanna, Sonia; Dutta, Alak K; Parvin, Sayma; Biswas, Sunil K; Howlader, M Zakir H (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Carbohydrate rich food is the most widely consumed nutrient globally, but when consumed in excess it can have undesirable effects on health. Glycemic index (GI) could be a degree of the impacts of carbohydrates on blood glucose levels. Materials and methods: We selected eight Bangladesh Rice Research Institute (BRRI) developed varieties and two local varieties. Results and Discussion: The highest amount of carbohydrate was measured in BRRI Dhan-29 variety (81.18%), and the lowest amount was found in BR-26 (78.03%). The highest starch digestibility was found in BRRI Dhan-40 (86.56%), and the lowest starch digestibility was found in BRRI Dhan-28 (70.20%).GI ranged from 49.87 to 74.20 in parboiled varieties. Only two varieties (BR-16 and Pajam) are in the low GI group (55 and below), with most of the varieties are within medium GI group (56-69) (BR-11, BR-26, BRRIDhan-28, BRRIDhan-30 and BRRIDhan-40). High GI value (70 and above) are BRRI Dhan-29 and Chinigura. Although BR-16 had the highest amylose content and lowest GI value, however, in some cases, for example, BRRI-Dhan-29 has high amylose content as well as a high GI value. There was no significant correlation between GI and amylose content. However, when the elevated rapidly digestible starch value of BRRI Dhan-29 is being considered, at that point, it clarifies the higher GI value. A noteworthy relationship (r=0.62, p< 0.01) was found between GI values and RDS content. Conclusion: Low GI rice with good nutritional composition may encourage farmers as well as consumers for their high demand and economic benefit. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 484-490